1991
DOI: 10.1177/00220345910700061001
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Structure of the 23S Ribosomal RNA Molecule in Certain Oral Bacteria

Abstract: Ribosomal RNA (rRNA) isolated from Wolinella recta and seven related bacteria was examined by agarose gel electrophoresis. The 23S rRNA molecule could not be detected in W. recta, Wolinella curva, Bacteroides gracilis, or Bacteroides ureolyticus. In place of the 23S molecule, there were three smaller molecules of approximately 1700, 650, and 600 bases designated 23S alpha, 23S beta, and 23S delta, respectively. An intact 23S rRNA molecule could be isolated from Wolinella succinogenes, Campylobacter concisus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Whilst the S. typhimurium and Y enterocolitica 23S rRNA gene IVs are small and noncoding, the larger IVSs found in Leptospira vary from 485 to 759 nts and contain a small ORF (121-133 amino acids) oriented so that the sense strand appears in the transcript rRNA (24). It was earlier observed that the 23S rRNA appears as three smaller molecular species in Wolinella recta (Campylobacter rectus), W.curva (C. curvus), Bacteroides gracilis and B. ureolyticus (25), four species belonging to RNA Superfamily VI (4), which also contains the genus Helicobacter.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the S. typhimurium and Y enterocolitica 23S rRNA gene IVs are small and noncoding, the larger IVSs found in Leptospira vary from 485 to 759 nts and contain a small ORF (121-133 amino acids) oriented so that the sense strand appears in the transcript rRNA (24). It was earlier observed that the 23S rRNA appears as three smaller molecular species in Wolinella recta (Campylobacter rectus), W.curva (C. curvus), Bacteroides gracilis and B. ureolyticus (25), four species belonging to RNA Superfamily VI (4), which also contains the genus Helicobacter.…”
Section: Discussionmentioning
confidence: 99%
“…Photograph of rRNA specimens isolated from single colonies of clinical isolates of A. actinomycetemeomitans (lanes 1 and 4), H. apinofyliilus (lanes 2, 3) and H. .segnis (lanes 5, 6) grown on blood agar (lanes 1,2,5) and chocolate agar (lanes 3, 4, 6). dopseudomonas sphaeroides (16), Agrobacteriutn tutnefacietis (6), Bdellovibrio bacteriovorus (19), Bacteroides graeilis and Bctcteroides ureolytieus (30) and the oral bacteria Campylobacter rectus and Catnpylobacter curva (30). However, no other bacteria growing on TSBV selective medium and resembling A. actitiomyeetemeotnitatis in colony morphology or catalase reactivity exhibited the same rRNA pattern as A. actinomycetetncotnitans.…”
mentioning
confidence: 98%